2021
DOI: 10.1007/s12369-021-00841-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive Turn in Elder-Care Workers’ Views Toward Telecare Robots

Abstract: Robots have been slowly but steadily introduced to welfare sectors. Our previous observations based on a large-scale survey study on Finnish elder-care workers in 2016 showed that while robots were perceived to be useful in certain telecare tasks, using robots may also prove to be incompatible with the care workers’ personal values. The current study presents the second wave of the survey data from 2020, with the same respondents (N = 190), and shows how these views have changed for the positive, including hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
0
17
0
4
Order By: Relevance
“…Ways to address the core relational foundations of care ethics were visible in some articles that showed the impact of care technologies in everyday care practices and relations [23,32,38], while comparisons of conflicting underpinnings for caregiving practices were made visible by others [35,37]. Interestingly, several authors argued that care ethical theory needs development and expansion to encompass technologies and the non-human aspects of care and suggested reframing care ethics as 'occupational ethics' [39] and 'empirical ethics' [30]. Although we appreciate this turn of attention, such calls for the expansion of care ethical theory [29,31] risk undercommunicating the ways in which the ethics of care framework already manifests as highly relevant within all kinds of relations, including technology-mediated ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ways to address the core relational foundations of care ethics were visible in some articles that showed the impact of care technologies in everyday care practices and relations [23,32,38], while comparisons of conflicting underpinnings for caregiving practices were made visible by others [35,37]. Interestingly, several authors argued that care ethical theory needs development and expansion to encompass technologies and the non-human aspects of care and suggested reframing care ethics as 'occupational ethics' [39] and 'empirical ethics' [30]. Although we appreciate this turn of attention, such calls for the expansion of care ethical theory [29,31] risk undercommunicating the ways in which the ethics of care framework already manifests as highly relevant within all kinds of relations, including technology-mediated ones.…”
Section: Discussionmentioning
confidence: 99%
“…One explored moral competence and hope in caring relations [35], whereas another considered the specific ethical complexities in social networking interventions [29]. A third article explored workshop methodologies for developing collaborations involving care values [33], while the last surveyed a change in care workers' views of care robots due to variations in the value-based assessment of robot use [39].…”
Section: Identification Of Studies Via Databases and Registersmentioning
confidence: 99%
See 2 more Smart Citations
“…Care robots would not be the exception. A recent survey carried out in Finland demonstrated that conventionally negative views held by eldercare professionals toward telecare robots took a positive turn during the pandemic ( 97 ). It remains to be seen whether this trend is observed across Europe.…”
Section: Discussionmentioning
confidence: 99%